Understanding Degassing Pathways Along the 1886 Tarawera (New Zealand) Volcanic Fissure by Combining Soil and Lake CO2 Fluxes - Hughes, Ery C.; Mazot, Agnes; Kilgour, Geoff; Asher, Cameron; Michelini, Marco; Britten, Karen; Chardot, Lauriane; Feisel, Yves; Werner, Cynthia (Frontiers in Earth Science, 2019)
The 1886 eruption of Tarawera, New Zealand, produced a ~17 km long fissure across the Tarawera Volcanic Complex (TVC), Lake Rotomahana (LR), and the Waimangu Geothermal System (WGS). We combine new soil CO2 flux and isotope measurements of TVC with previous data from LR and WGS to fingerprint the CO2 source, understand the current pathways for degassing, and quantify the CO2 released along the entire fissure. The total CO2 emissions from the fissure are 1227 t·d-1 (742–3398 t·d-1). The CO2 flux from WGS and LR is far higher than from TVC (>549 vs. ~4 t·d-1 CO2), likely influenced by a shallow silicic body at depth and caldera rim faults increasing permeability at the southern end of the fissure. Highly localised regions of high CO2 flux occur along the fissure and are likely caused by cross-cutting faults that focus the flow. One of these areas occurs in the TVC, which is emitting ~1 t·d-1 CO2 with a δ13CO2 of -5.5 ± 0.5 ‰, and comparison with previous observations shows that activity is declining over time. Future CO2 flux surveys could be compared to this baseline survey to understand changes in volcanic activity.